PENGARUH PARTISISPASI ANGGARAN TERHADAP KINERJA APARAT PEMERINTAH DENGAN KOMITMEN ORGANISASI DAN PERSEPSI INOVASI SEBAGAI VARIABEL INTERVENING (Studi Empiris Pada Pemerintah Kota Pekanbaru) - Barnes Ar; Novita Novita; Azhari Azhari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research aims to test the influence of the participation of government officials performance against the budget on the Organization of the public sector. The study also tested the commitment of the Organization and the perceptions of the relationship between variables as innovation influence the participation of government officials performance against budget. The collection of data in this study using questionnaire. The population in this research is 43 OPD (Organization device area) in the city of Pekanbaru. samples taken is 22 OPD. The respondents in this study is the Echelon 2.3, 4, Questionnaires submitted to 66 structural OPD officer city of Pekanbaru, 80.30% questionnaire returned and 80.30% questionnaires filled out in full and can be processed. Methods of Data analysis used in this study is the analysis of the line to test the influence of the participation of government officials ' performance against the budget with organizational commitment and innovation as intervening variable perception using SPSS 21.0. The results of this study found that the presence of the influence of the participation of government officials performance against budget. Participation also has budget significantly to organizational commitment. However, the participation of the budget does not affect the performance of the apparatus of the Government through innovation as intervening variable perception.Keywords : budgetary participation, performance of government apparatus, commitment of organization, perception of innovation, and public sector organization.